Glomerular diseases: podocyte hypertrophy mismatch and glomerular disease - Kriz, Wilhelm (Nature reviews. Nephrology, 2012)
Cell hypertrophy is the only mechanism by which podocytes can cope with increased functional demands, whereas other glomerular cells can adapt by cell proliferation. In the setting of systemically stimulated glomerular growth, a 'mismatch' of inadequate podocyte hypertrophy and overall glomerular growth may lead to podocyte loss and development of focal segmental glomerulosclerosis.
Gesehen am 16.04.2018